REFORMULATION OF THE RELATIONSHIP BETWEEN ZAKAT AND TAX IN THE ISLAMIC FISCAL SYSTEM: A THEMATIC STUDY OF THE QUR’AN AND HADITH IN THE INDONESIAN CONTEXT - TB Rifat; Basyarudin; Eko Bambang Rahmono; Ahmad Pathonih; Asep Mustopa Kamal (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Indonesia faces a dualism within the Islamic fiscal system, where zakat and taxes operate separately without clear integration. This condition raises fundamental questions regarding the relationship between the two from a sharia perspective and their implications for fiscal justice among Indonesian Muslims. This study aims to examine and formulate the relationship between zakat and taxes from the perspective of the Qur’an and Hadith in order to produce an applicable reformulation model within the context of Indonesia’s fiscal system. This research employs a qualitative approach using a thematic (maudhu‘i) method applied to primary Islamic texts. Qur’anic verses and Hadiths related to zakat, taxation (kharaj, jizyah, ‘usyur), and fiscal obligations were collected, classified, and comprehensively analyzed to identify the underlying connection between the two. The analysis is further supported by a study of maqashid al-shariah and contemporary ijtihad of Indonesian scholars. This study seeks to produce a reformulation model of the zakat–tax relationship through three possible schemes: (1) a partial substitution model, in which zakat can serve as a deduction for income tax up to a certain limit; (2) a complementary model, positioning zakat as a religious obligation and tax as a civic obligation with distinct functions; and (3) a progressive integrative model, integrating zakat into the national fiscal system through a more comprehensive tax incentive mechanism. The findings indicate that the Qur’an and Hadith provide a flexible foundation for all three models, depending on the context of maslahah and public interest.